Frequency and prediction of persistent urinary tract dilation in third trimester and postnatal urinary tract dilation in infants following diagnosis in second trimester. (1st April 2022) - Green, C. A.; Adams, J. C.; Goodnight, W. H.; Odibo, A. O.; Bromley, B.; Jelovsek, J. E.; Stamilio, D. M.; Venkatesh, K. K.
ABSTRACT: Objective: To determine the frequency, associated characteristics and prognostic value of the current risk stratification system for prenatal urinary tract dilation (UTD) for predicting persistent UTD in the third trimester and subsequent postnatal UTD in the infant, following diagnosis in the second trimester. Methods: This was a single‐institution retrospective cohort study of singleton pregnancies diagnosed with unilateral or bilateral UTD in the second trimester (before 28 weeks' gestation) with follow‐up in the third trimester (at or after 28 weeks) between January 2017 and May 2019. In all cases, the prenatal diagnosis and stratification to low‐risk (Grade A1) or increased‐risk (Grade A2–3) UTD was made using the 2014 UTD consensus classification system. The primary outcomes included persistent prenatal UTD in the third trimester and postnatal UTD up to 6 months of age. We performed multivariable analysis to assess whether patient and second‐ and third‐trimester sonographic characteristics (such as UTD laterality, other renal abnormality (calyceal dilation, abnormal parenchymal appearance, abnormal ureter or bladder) and anteroposterior renal pelvic diameter (AP‐RPD)) were associated with the study outcomes. We assessed the predictive value of the current risk stratification system (Grade A1 vs Grade A2–3) in the second and third trimesters for persistent prenatal UTD and postnatal UTD using the area under the receiver‐operating‐characteristics curve (AUC). Results: Of 26 620 second‐trimester ultrasound assessments in the study period, 347 patients were diagnosed with UTD in the second trimester and had third‐trimester follow‐up, of whom 150/347 (43% (95% CI, 38–49%)) had persistent UTD in the third trimester. Among the 282/347 (81%) patients with postnatal follow‐up available, the frequency of postnatal UTD was 49/282 (17% (95% CI, 13–22%)), and among the subset with persistent UTD in the third trimester, the frequency of postnatal UTD was 46/102 (45% (95% CI, 35–55%)). The most frequent postnatal diagnosis was transient UTD (76%), followed by duplicated collecting system (10%). Of infants originally diagnosed with UTD in the second trimester, 2% (7/347) required surgery; stated differently, of the 49 infants with postnatal UTD, 14% (7/49) required surgery. At second‐trimester diagnosis, sonographic predictors of both persistent prenatal UTD and postnatal UTD included the presence of other renal abnormality and UTD Grade A2–3. At third‐trimester follow‐up, predictors of postnatal UTD were larger mean AP‐RPD and UTD Grade A2–3, while all cases had other renal abnormality. Second‐trimester diagnosis of UTD Grade A2–3 had satisfactory discrimination for predicting persistent prenatal UTD (AUC, 0.64 (95% CI, 0.58–0.70)) and postnatal UTD (AUC, 0.72 (95% CI, 0.63–0.81)), as did third‐trimester UTD Grade A2–3 for predicting postnatal UTD (AUC, 0.66 (95% CI, 0.56–0.76)). Conclusions: The majority of cases of prenatal UTD did not result in postnatal UTD, and of those that did, very few required surgery. Follow‐up third‐trimester assessment after a second‐trimester diagnosis of UTD is warranted. The current risk stratification system by UTD grade, based on the 2014 UTD consensus classification, can be used to predict postnatal UTD with fair accuracy. Further research is needed to determine whether the predictive performance of this system can be improved by incorporating additional risk factors. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.